A Review of Classical Swine Fever Virus and Routes of Introduction into the United States and the Potential for Virus Establishment - Brown, Vienna R. (Front Vet Sci, 2018)
Classical swine fever (CSF) is caused by CSF virus (CSFV) which can be the source of substantial morbidity and mortality events in affected swine. The disease can take one of several forms (acute, chronic, or prenatal) and depending on the virulence of the inoculating strain may result in a lethal infection irrespective of the form acquired. Because of the disease-free status of the United States and the high cost of a viral incursion, a summary of US vulnerabilities for viral introduction and persistence is provided. The legal importation of live animals as well as animal products, byproducts, and animal feed serve as a potential route of viral introduction. Current import regulations are described as are mitigation strategies that are commonly utilized to prevent pathogens, including CSFV, from entering the US. The illegal movement of suids and their products as well as an event of bioterrorism are both feasible routes of viral introduction but are difficult to restrict or regulate. Ultimately, recommendations are made for data that would be useful in the event of a viral incursion. Population and density mapping for feral swine across the United States would be valuable in the event of a viral introduction or spillover; density data could further contribute to understanding the risk of infection in domestic swine. Additionally, ecological and behavioral studies, including those that evaluate the effects of anthropogenic food sources that support feral swine densities far above the carrying capacity would provide invaluable insight to our understanding of how human interventions affect feral swine populations. Further analyses to determine the sampling strategies necessary to detect low levels of antibody prevalence in feral swine would also be valuable.